Eukaryotic translation initiation factor eIF4G2 opens novel paths for protein synthesis in development, apoptosis and cell differentiation - Liu, Yudi; Cui, Jiuwei; Hoffman, Andrew R.; Hu, Ji‐Fan (Cell proliferation, 2023)
Protein translation is a critical regulatory event involved in nearly all physiological and pathological processes. Eukaryotic translation initiation factors are dedicated to translation initiation, the most highly regulated stage of protein synthesis. Eukaryotic translation initiation factor 4G2 (eIF4G2, also called p97, NAT1 and DAP5), an eIF4G family member that lacks the binding sites for 5′ cap binding protein eIF4E, is widely considered to be a key factor for internal ribosome entry sites (IRESs)‐mediated cap‐independent translation. However, recent findings demonstrate that eIF4G2 also supports many other translation initiation pathways. In this review, we summarize the role of eIF4G2 in a variety of cap‐independent and ‐dependent translation initiation events. Additionally, we also update recent findings regarding the role of eIF4G2 in apoptosis, cell survival, cell differentiation and embryonic development. These studies reveal an emerging new picture of how eIF4G2 utilizes diverse translational mechanisms to regulate gene expression. Eukaryotic translation initiation factors 4G2 (eIF4G2) participates in diverse translation initiation, including translation driven by internal ribosome entry sites (IRESs), cap‐independent translation enhancers (CITEs), and N6‐methyladenosine (m6A), as well as in non‐canonical eIF4F‐independent cap‐dependent translation and canonical cap‐dependent scanning translation initiation. Through the translational mechanisms to regulate gene expression, eIF4G2 is significantly involved in apoptosis, cell survival, cell differentiation, and embryonic development processes.